A study of the antioxidant system of Apis mellifera larvae treated with Paenibacillus larvae - Moliné, Maria de la Paz (2022)
The impact on the integrity of epithelium tissues caused by Paenibacillus larvae in Apis mellifera larvae affected by American foulbrood (AFB) disease may generate oxidative stress. However, the relation between AFB and the oxidative stress status of the larvae remains unknown. In this study, we provide the first evidence that inoculation with P. larvae spores on in vitro reared larvae disturbs the balance between pro-oxidants and antioxidants, influencing enzymatic activity and producing lipid peroxidation. We suggest that the oxidative stress observed in larvae treated with P. larvae would constitute a cytotoxic additional factor, besides virulence components, in the AFB progress.